Differences in Family Immunity in Preventing the Spread of Infection in Healthy Families and Confirmed COVID-19 - Mukarromah, Nur; Badriyah, Fatin Lailatul; Zakaria, Achmad; Priyantini, Diah (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Coronavirus Disease 2019 (COVID-19) causes social transformations that can shake the existence of individuals and families so that they become vulnerable or have the potential to not have Family Immunity. Objectives: The purpose of this study was to analyze differences in family immunity in preventing the spread of infection in healthy and confirmed families of COVID-19. Methods: A case control research design to compare two groups regarding family immunity to the prevention of COVID-19 infection, which was carried out in the city of Surabaya, Indonesia in August 2021 – March 2022. A total of 104 respondents were recruited using convenience sampling. Data were collected using a questionnaire and analyzed using SPSS version 21 with Chi Square test. Results: Family immunity shows better results in healthy families with 43.3% better family belief system status, 28.8% good organizational patterns, 38.5% better communication process and 36.5% better Controlling the spread of infectious disease. The results of the significance test showed that all P values 0.05 and calculated X2 results > X2, it can be concluded that all indicators are related to family COVID-19 status and can explain the family immunity variable. Conclusion: Family immunity in the healthy family group and the confirmed COVID-19 group showed different results, families with healthy conditions had much better family immunity than families who had confirmed COVID-19.